Performance Practice and Interpretative Insights in Brahms' Op. 118 No. 2 - Liu, Tianqing (Pacific International Journal, 2024)
This paper explores the performance practice and interpretative insights necessary for understanding and effectively performing Johannes Brahms' Intermezzo in A major, Op. 118 No. 2. By examining the historical context, structural and theoretical elements, and characteristics of Romantic piano performance, the study provides a comprehensive guide for pianists. It addresses technical challenges, practice strategies, and the balance between personal expression and fidelity to the score. The research highlights the enduring significance of Op. 118 No. 2 and offers practical approaches for performers and educators, emphasizing the importance of historical understanding and emotional expressiveness in interpreting Brahms’ work.